Atypical granular cell tumor of the urinary bladder: A case report and literature review - Antonio Tufano; Vittorio Canale; Giovanni Di Lascio; Giulia Coppola; Rocco Simone Flammia; Cristiano Cristini (Urology Case Reports, 2021)
Granular cell tumors (GCTs) are rare neoplasms of neural origin and usually tend to have a benign behaviour. We report a case of a 54 years old woman with severe gross hematuria caused by an atypical granular cell tumor which was successfully managed with a transurethral resection of the bladder (TURB). No local recurrence was observed after a three-year follow-up. The appropriate histological characterization and subclassification (benign, atypical and malignant neoplasm) is mandatory for an optimal patient management, in order to offer an appropriate treatment and a correct follow-up.